2014
DOI: 10.1264/jsme2.me14052
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria of the Candidate Phylum TM7 are Prevalent in Acidophilic Nitrifying Sequencing-Batch Reactors

Abstract: Laboratory-scale acidophilic nitrifying sequencing-batch reactors (ANSBRs) were constructed by seeding with sewage-activated sludge and cultivating with ammonium-containing acidic mineral medium (pH 4.0) with or without a trace amount of yeast extract. In every batch cycle, the pH varied between 2.7 and 4.0, and ammonium was completely converted to nitrate. Attempts to detect nitrifying functional genes in the fully acclimated ANSBRs by PCR with previously designed primers mostly gave negative results. 16S rRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 81 publications
(111 reference statements)
2
19
0
1
Order By: Relevance
“…While candidate Division TM7 DNA has been reported from soil, freshwater, hot springs and termite guts, this group of bacteria has been referred to as biology's Bdark matter^due to the lack of axenic cultures for physiological examination (Dinis et al 2011). However, sequencing has shown that these strains harbor genes for nitrification and chitinase, which could be beneficial to E+ plants (Hanada et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…While candidate Division TM7 DNA has been reported from soil, freshwater, hot springs and termite guts, this group of bacteria has been referred to as biology's Bdark matter^due to the lack of axenic cultures for physiological examination (Dinis et al 2011). However, sequencing has shown that these strains harbor genes for nitrification and chitinase, which could be beneficial to E+ plants (Hanada et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Purified isolates were preserved in RPL2 agar medium as stub cultures. The 16S rRNA genes from the cell lysate [36] were PCR-amplified with bacterial universal primers 27f and 1492r (see Table S1) [37] and sequenced by the Sanger method using a cycle sequencing kit and an automated DNA sequencer [38]. Sequence data were compiled using the GENETYX-MAC program (GENETYX, Tokyo, Japan) and subjected to EzBioCloud [39] and BLAST [40] homology searches for phylogenetic identification.…”
Section: Isolation and Phylogenetic Identification Of Pnsbmentioning
confidence: 99%
“…Saccharibacteria (former candidate division TM7, also called candidate phylum Saccharibacteria) is frequently found in various natural environments and activated sludge which makes it a beneficial candidate phylum [29]. However, Hanada [45] also reported the prevalence of candidate division TM7 in an acidophilic nitrified SBR (sequencing batch reactor) which was added to simulative wastewater made up of ammonium and other salts without a carbon source. Interestingly, Zhao [46] reported that the most suitable salinity for candidate division TM7 is 2%, which is very close to the salinity in the SGBRs.…”
Section: Evolution Of Bacterial Community Structurementioning
confidence: 99%